2020
DOI: 10.1177/1747021820970079
|View full text |Cite
|
Sign up to set email alerts
|

Balancing cognitive and environmental constraints when deciding to switch tasks: Exploring self-reported task-selection strategies in self-organised multitasking

Abstract: We investigated how people balance cognitive constraints (switch costs) against environmental constraints (stimulus availabilities) to optimize their voluntary task switching performance and explored individual differences in their switching behaviour. Specifically, in a self-organized task-switching environment, the stimulus needed for a task repetition was delayed by a stimulus-onset asynchrony (SOA) that increased with each consecutive repetition until a task switch reset the SOA. As predicted, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…where the participant is allowed to perform the same task as often as they prefer), future research should consider the use of the self-organized task-switching paradigm (Mittelstädt et al, 2018), as in several recent studies, this paradigm was found to be powerful enough to MIND WANDERING AND COGNITIVE FLEXIBILITY 22 induce high levels of voluntary task-switching behavior (a mean switch rate of 16% to 49%; Mittelstädt et al, 2018;2019;Mittelstädt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…where the participant is allowed to perform the same task as often as they prefer), future research should consider the use of the self-organized task-switching paradigm (Mittelstädt et al, 2018), as in several recent studies, this paradigm was found to be powerful enough to MIND WANDERING AND COGNITIVE FLEXIBILITY 22 induce high levels of voluntary task-switching behavior (a mean switch rate of 16% to 49%; Mittelstädt et al, 2018;2019;Mittelstädt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A finding that is also consistent with research from introspection in multitasking showing that people are aware of their switch costs ( Bratzke and Bryce, 2019 ). Besides, it was shown that individuals are even able to take these costs into account in their task selection behavior ( Mittelstädt et al, 2018 , 2019 , 2021 ; Monno et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aspect of interindividual differences in multitasking has increasingly received attention in recent years (see, e.g., Laguë-Beauvais et al, 2013 ; Reissland and Manzey, 2016 ; Heidemann et al, 2020 ; Kubik et al, 2020 ; Mittelstädt et al, 2021 ). Meanwhile, several studies support the existence and relevance of interindividual differences in strategies with which individuals prefer to cope with multiple tasks (e.g., Damos et al, 1983 ; Reissland and Manzey, 2016 ; Brüning and Manzey, 2018 ; Brüning et al, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, a smaller overlap in task representations allows participants to keep the two tasks more equally activated because it reduces task confusion. Following others (e.g., Fröber & Dreisbach, 2017 ; Mittelstädt et al, 2021 ), this should counteract the strong preference to select task repetition and increase switching behavior. Thus, for our initial (preregistered) Experiment 1 using the adaptive VTS paradigm without randomness instruction, we assumed that less overlap in effector-specific task representation account would predict larger switch rates in the task-to-hand compared to the task-to-finger mapping condition.…”
Section: Effector-specific Task Representations In Voluntary and Exte...mentioning
confidence: 99%
“…Note that the sample size of 48 participants was somehow arbitrary set, because we had no information about the possible effects size and we wanted to compensate for potential dropouts. Note, however, that no participants had to be excluded when applying the same data exclusion criteria as in a previous study ( Mittelstädt et al, 2019 ; Mittelstädt et al, 2021 ).…”
mentioning
confidence: 99%